Managing Elevated Risk Global Liquidity, Capital Flows, and Macroprudential Policy-An Asian Perspective - Azis, Iwan J.; Shin, Hyun Song (Springer Nature Singapore : Imprint: Springer, 2015)
This book discusses the risks and opportunities that arise in Emerging Asia given the context of a new environment in global liquidity and capital flows. It elaborates on the need to ensure financial and overall economic stability in the region through improved financial regulation and other policy measures to minimize the emergent risks. "Managing Elevated Risk: Global Liquidity, Capital Flows, and Macroprudential Policy-An Asian Perspective" also explores the range of policy options that may be deployed to address the impact of global liquidity on domestic financial and socio-economic conditions including income inequality. The book is primarily aimed at policy makers, financial market regulators and supervisory agencies to help them improve national regulatory systems and to promote harmonization of national regulations and practices in line with global standards. Scholars and researchers will also gain important information and knowledge about the overall impacts of changing global liquidity from the book.